Genetic diversity and candidate genes for transient waterlogging tolerance in mungbean at the germination and seedling stages - Kyu, Khin Lay; Taylor, Candy M.; Douglas, Colin Andrew; Malik, Al Imran; Colmer, Timothy David; Siddique, Kadambot H. M.; Erskine, William (Frontiers Media, 2024)
Mungbean [ Vigna radiata var. radiata (L.) Wilczek] production in Asia is detrimentally affected by transient soil waterlogging caused by unseasonal and increasingly frequent extreme precipitation events. While mungbean exhibits sensitivity to waterlogging, there has been insufficient exploration of germplasm for waterlogging tolerance, as well as limited investigation into the genetic basis for tolerance to identify valuable loci. This research investigated the diversity of transient waterlogging tolerance in a mini−core germplasm collection of mungbean and identified candidate genes for adaptive traits of interest using genome−wide association studies (GWAS) at two critical stages of growth: germination and seedling stage (i.e., once the first trifoliate leaf had fully−expanded). In a temperature−controlled glasshouse, 292 genotypes were screened for tolerance after (i) 4 days of waterlogging followed by 7 days of recovery at the germination stage and (ii) 8 days of waterlogging followed by 7 days of recovery at the seedling stage. Tolerance was measured against drained controls. GWAS was conducted using 3,522 high−quality DArTseq−derived SNPs, revealing five significant associations with five phenotypic traits indicating improved tolerance. Waterlogging tolerance was positively correlated with the formation of adventitious roots and higher dry masses. FGGY carbohydrate kinase domain−containing protein was identified as a candidate gene for adventitious rooting and mRNA-uncharacterized LOC111241851, Caffeoyl-CoA O-methyltransferase At4g26220 and MORC family CW-type zinc finger protein 3 and zinc finger protein 2B genes for shoot, root, and total dry matter production. Moderate to high broad−sense heritability was exhibited for all phenotypic traits, including seed emergence (81%), adventitious rooting (56%), shoot dry mass (81%), root dry mass (79%) and SPAD chlorophyll content (70%). The heritability estimates, marker−trait associations, and identification of sources of waterlogging tolerant germplasm from this study demonstrate high potential for marker−assisted selection of tolerance traits to accelerate breeding of climate−resilient mungbean varieties.